The Role of Islamic Education In The Struggle For Palestine Independence: History of Resistance and Education Under Israel Opposition - Januar; Alfi Rahmi; Al Ihksan; Md Noor Bin Hussin (TADRIS: Jurnal Pendidikan Islam, 2024)
This research aims to find out the history of the Palestinian struggle and the close relationship between Islamic education and the struggle for independence. In addition, this research explores the role of education as a source of strength, how the struggle for independence is reflected in the curriculum, and the challenges and hopes of Islamic education in Palestine. The research method used is a qualitative descriptive approach, which makes it possible to explore and explain the contribution of Islamic education to the Palestinian struggle. Research methods include document analysis, literature study, and interviews with Islamic education experts. In this case, those interviewed were Islamic Education experts from UIN Sjech M. Djamil Djambek Bukittinggi and Islamic Education experts from UIN Arraniry Banda Aceh. The research results show that Islamic education had a key role in the struggle for independence under Israeli occupation, despite facing significant challenges such as access restrictions, school closures, and limited resources. Even so, Islamic education remains an important force in maintaining the spirit of struggle, nurturing cultural identity, and connecting the young Palestinian generation with the history of their struggle. The educational curriculum reflects the values ​​of struggle and justice, which are the motivation for efforts to achieve independence. Amid ongoing conflict and pressure resulting from the occupation, education remains one of the main pillars of maintaining Palestinian identity and advancing the ideals of independence.